Upper esophageal sphincter mechanical states analysis: a novel methodology to describe UES relaxation and opening - Omari, Taher I.; Wiklendt, Lukasz; Dinning, Philip; Costa, Marcello; Rommel, Nathalie; Cock, Charles (Frontiers in Systems Neuroscience, 2015)
The swallowing muscles that influence upper esophageal sphincter (UES) opening are centrally controlled and modulated by sensory information. Activation of neural inputs to these muscles, the intrinsic cricopharyngeus muscle and extrinsic suprahyoid muscles, results in their contraction or relaxation, which changes the diameter of the lumen, alters the intraluminal pressure and ultimately inhibits or promotes flow of content. This relationship that exists between the changes in diameter and concurrent changes in intraluminal pressure has been used previously to calculate the ‘mechanical states’ of the muscle; that is when the muscles are passively or actively, relaxing or contracting. Diseases that alter the neural pathways to these muscles can result in weakening the muscle contractility and/or decreasing the muscle compliance, all of which can cause dysphagia. Detecting these changes in the mechanical state of the muscle is difficult and as the current interpretation of UES motility is based largely upon pressure measurement (manometry), subtle changes in the muscle function during swallow can be missed. We hypothesised that quantification of mechanical states of the UES and the pressure-diameter properties that define them, would allow objective characterisation of the mechanisms that govern the timing and extent of UES opening during swallowing. To achieve this we initially analysed swallows captured by simultaneous videofluoroscopy and UES pressure with impedance recording. From these data we demonstrated that intraluminal impedance measurements could be used to determine changes in the internal diameter of the lumen when compared to videofluoroscopy. Then using a database of pressure-impedance studies, recorded from young and aged healthy controls and patients with motor neuron disease, we calculated the UES mechanical states in relation to a standardised swallowed bolus volume, normal aging and dysphagia pathology. Our results indicated that eight